The Relationship between Big Five Personality and Soft Skills among Graduate Unemployment - Begum Bathusha Hamid, Mehrunishah; Kumar Moona Haji Mohamed, Ramesh; Raj Devarajoo, Aruna; Mani, Rajaletchumy; Siti Lazrina Md Lazim, Che (International Journal of Psychosocial Rehabilitation, 2020)
Soft skills include aspects of generic skills. Although there is no specific skill list on soft skills, most of them relate to skills acquisition such as leadership, teamwork, communication, and continuous learning. Soft skills are often associated with individual personality traits by psychologists. The purpose of this current research is to investigate the positive relationship between soft skills and Big Five personality among unemployed graduates. Purposive convenient sampling was conducted on the target population with a sample size of 293 thought peninsular of Malaysia. The result shows clearly that unemployment among graduates is due to low teamwork and communication skills and neuroticism, as their extraversion is low and high neuroticism. The future research and limitations of the study have been discussed.